Emotional attention capture by facial expressions - Sawada, Reiko (Sci Rep, 2015)
Previous studies have shown that emotional facial expressions capture visual attention. However, it has been unclear whether attentional modulation is attributable to their emotional significance or to their visual features. We investigated this issue using a spatial cueing paradigm in which non-predictive cues were peripherally presented before the target was presented in either the same (valid trial) or the opposite (invalid trial) location. The target was an open dot and the cues were photographs of normal emotional facial expressions of anger and happiness, their anti-expressions and neutral expressions. Anti-expressions contained the amount of visual changes equivalent to normal emotional expressions compared with neutral expressions, but they were usually perceived as emotionally neutral. The participants were asked to localize the target as soon as possible. After the cueing task, they evaluated their subjective emotional experiences to the cue stimuli. Compared with anti-expressions, the normal emotional expressions decreased and increased the reaction times (RTs) in the valid and invalid trials, respectively. Shorter RTs in the valid trials and longer RTs in the invalid trials were related to higher subjective arousal ratings. These results suggest that emotional facial expressions accelerate attentional engagement and prolong attentional disengagement due to their emotional significance.